Islamic Human Capital Strategies for Preventing Fraud in Sharia Cooperatives - Sari, Yuli Indah; bin Mislan Cokrohadisumarto, Widiyanto (IJIBE (International Journal of Islamic Business Ethics), 2024)
The issue of internal fraud remains a hindrance to the development of this Sharia cooperative. Preventive measures with a new approach are necessary early on to address fraud. This research aims to find a practical model of the role of Islamic human capital development in preventing internal fraud at Sharia cooperatives. The study utilized a qualitative approach with a sample of 7 Baitul Tamwil Muhammadiyah (BTM) affiliated with the Central Java branch of Pusat BTM, Indonesia, selected through purposive sampling. The research results identified a practical model of Islamic human capital development and its role in preventing fraud in the Sharia cooperative. This includes efforts to build an Islamic environment, incorporate Islamic values into operational regulations, foster knowledge sharing, organize structured and independent training, and identify other factors involved in Islamic human capital development. Spiritual, knowledge, moral, and behavioural approaches were employed to reduce fraud and loss frequency and enhance employee performance.